A. Konecny and N. Sekunda (eds) The Battle of Plataiai 479 BC. - Dickinson, Oliver (Journal of Greek Archaeology, 2023)
pp. 296. Vienna: Phoibos Verlag, 2022. ISBN 978-3-85161-271-4 (hardback), 978-3-85161-272-1 (e-pdf). £73.70 reduced to £66.45 (according to Amazon).